The Generalization of Conscious Attentional Avoidance in Response to Threat Among Breast Cancer Women With Persistent Distress - Ng, Danielle Wing Lam; Fielding, Richard; Lam, Wendy Wing Tak (Frontiers in Psychology, 2020)
Objectives: Following breast cancer (BC), women with persistent distress previously exhibited attentional bias (AB) away from supraliminally-presented cancer- or threat-related information, responses consistent with avoidance coping, and showed negative interpretation bias. Here we attempt to characterize the nature of supraliminal AB and interpretation bias in this subset of women in comparison with healthy controls. Methods: Extending our previous work, we compared AB patterns for supraliminally-presented negatively-valenced words and cancer-related information (CRI) assessed by modified dot-probe tasks, and negative interpretation bias assessed by an ambiguous cue task between 140 BC women previously identified as featuring low-stable or persistent high distress and 150 age-matched non-BC healthy controls having HADS-defined low or high distress (HADS scores >8). Results: Attentional avoidance of non-cancer related negatively-valenced words was seen among the anxious BC group, while heightened attention towards such words was seen in anxious healthy controls; F(3, 286)=4.24, p=0.006. However, all anxious women in both BC and healthy groups directed attention away from CRI under supraliminal conditions. Comparable, but non-significant AB patterns were seen in depressed women of both groups. Interpretation bias scores were significantly higher in BC women with high anxiety vs healthy controls with high anxiety; F(3, 286)=14.91, p<0.001. Conclusion: Women with high distress generalized conscious attentional avoidance responses to negatively-valenced stimuli, indicating likely hypersensitivity to potential threat in ambiguous cues and exaggerated threat perception. This may cause (or reflect) maladaptive emotional regulation. Attention focus training, reducing threat salience or modifying threat appraisal may help women alleviate distress levels after BC.